Making Unit Cost in Production Process More Accurate â€“ the Role of Queueing - Molnar, Viktor; Tumik, Abel (International Journal of Engineering and Technology, 2018)
Queueing is a general phenomenon in the life of almost every organization. Not only people but also processes connecting to manufacturing, machine maintenance, food delivery etc. can be modeled by queueing theory. Queueing always contains waiting waste and the latest management approaches endeavor to eliminate all wastes from the system. This paper introduces and demonstrates a solution based on Activity-Based Costing that aids in the more accurate identification of wastes and therefore in more accurate costing. An experiment was conducted in which queueing of products in a warehouse was analyzed. The queueing as waiting time was built in the ABC costing model. The paper highlights that the model supports thorough business-as-usual decision-making.Â Â